Bullous eruption as a cutaneous manifestation of eosinophilic granulomatosis with polyangiitis. Issue 1 (12th October 2021) - Tjokrosaputro, Paula P.; Lian, Tsui Y.; Wang, Dingyuan; Lee, Joyce S. S.; Xu, Chuanhui
Abstract: Cutaneous manifestations are variable in patients with eosinophilic granulomatosis with polyangiitis (EGPA). We report a case where bullous eruption was a presenting manifestation of EGPA. A 55‐year‐old Chinese man with a background of adult‐onset asthma and chronic sinusitis was admitted for a 3‐week history of lower limb weakness and a large bulla on his right calf with surrounding erythema. Skin biopsy showed a subepidermal blister with significant dermal eosinophilia, without vasculitis. The patient was diagnosed with EGPA with systemic involvement on the basis of a thorough medical history, eosinophilia, cardiac magnetic resonance imaging showing acute myocarditis, and nerve biopsy with eosinophilic vasculitic neuropathy. He responded well to corticosteroids and rituximab. Nonvasculitic bullous eruptions are rarely described as manifestations of EGPA. Prompt recognition of this entity is crucial for its early diagnosis. Key points: Bullous eruption is a rare cutaneous manifestation of EGPA. The heightened awareness and prompt recognition of the cutaneous manifestations are crucial for the early diagnosis of EGPA. Abstract : Bullous eruption as a cutaneous manifestation of eosinophilic granulomatosis with polyangiitis